1998
DOI: 10.3758/bf03201198
|View full text |Cite
|
Sign up to set email alerts
|

More than meets the eye: Context effects in word identification

Abstract: The influence of semantic context on word identification was examined using masked target displays, Related prime words enhanced a signal detection measure of sensitivity in making lexical decisions and in determining whether a probe word matched the target word. When line drawings were used as primes, a similar benefit was obtained with the probe task. Although these results suggest that contextual information affects perceptual encoding, this conclusion is questioned on the grounds that sensitivity in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 93 publications
3
59
1
Order By: Relevance
“…In this case, direct associative connections within the perceptual module could mediate the priming. Similar priming effects have, however, been obtained when picture primes were used (Masson & Borowsky 1998).…”
Section: Notessupporting
confidence: 73%
See 2 more Smart Citations
“…In this case, direct associative connections within the perceptual module could mediate the priming. Similar priming effects have, however, been obtained when picture primes were used (Masson & Borowsky 1998).…”
Section: Notessupporting
confidence: 73%
“…For example, in face priming study, the potential false alarm items were unfamiliar faces, which were not closely matched to the famous face targets. Similarly, in Masson and Borowsky's (1998) word priming study, potential false alarms came from nonwords that did not resemble the word targets. However, in Rhodes et al's (1993) word priming study, nonwords differed by only a single letter from their primed word counterparts.…”
Section: Cognitive Penetration: Would We Know It If We Saw It?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we should like to draw attention to a related debate on the impact of context on perceptual encoding. Several studies (e.g., Masson & Borowsky, 1998;Reinitz, Wright, & Loftus, 1989;Rhodes, Parkin & Tremewan, 1993) have shown that a semantically related prime can enhance a signal detection measure of performance such as d' across a range of different tasks. This has been taken to suggest that the semantically related prime increases the rate of feature extraction (Reinitz et al, 1989), and that the d' effect reflects a change in perceptual processing (Farah, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…2 ROUSE does not assume priming to result in a higher rate of feature extraction for the repeated stimulus (i.e., a perceptual effect). However, Huber et al (in press) did find a small but reliable benefit of associative priming when a prime word (e.g., MISTAKE) was associatively related to both choice words (e.g., ERROR and WRONG) compared to when the prime was not related to the choice words (see also Masson & Borowsky, 1998). Since the semantic overlap between prime and target is 100% for repetition priming, it is feasible that there might in fact be a semantic both-primed benefit in short-term repetition priming, albeit overshadowed by a much larger orthographic both-primed deficit.…”
Section: Remi: a Model For Long-term Primingmentioning
confidence: 99%